(untitled) (Development Service Industry Management, 2024)
In modern turbulent conditions, characterized by complex geopolitical and geoeconomic conditions and their impact on the functioning of the domestic economy, due to the emergence of many problems at all levels of anti-crisis management, there is an objective need to rethink the factors of anti-crisis management at the macro, meso and micro levels. The article defines the theoretical principles, functional content and directions for improvement of anti-crisis management as an integral element of the system of ensuring the economic security of enterprises. It is proved that anti-crisis management in the modern conditions of the development of the domestic economy has acquired special significance in the context of ensuring the economic security of enterprises. The implementation of the anti-crisis management system is possible taking into account the corporate culture and the presence of the following conditions, namely: the readiness of the implementation group, the participation of management, the availability of an implementation plan, obtaining an assessment of the current situation, and the availability of a policy on adaptive crisis management. It was determined that the main problem of low management efficiency is the lack of a preventive crisis management system at many enterprises. Grounded problematic aspects that determine the low effectiveness of anti-crisis management at enterprises. The peculiarity of anti-crisis management is to carry out extensive analytical work, since management decisions that determine the effectiveness of anti-crisis policy differ in the complexity of adoption. To improve anti-crisis management, it is necessary to constantly monitor the state of all affairs at the enterprise, timely and coordinated decision-making taking into account changes in the economic environment. The obtained results were used as a basis for the development of practical recommendations for improving the anti-crisis management system at domestic enterprises in order to strengthen and support their economic security.